Location of colon cancer (right-sided versus left-sided) as a prognostic factor and a predictor of benefit from cetuximab in NCIC CO.17. Issue 11 (July 2015) - Brulé, S.Y.; Jonker, D.J.; Karapetis, C.S.; O'Callaghan, C.J.; Moore, M.J.; Wong, R.; Tebbutt, N.C.; Underhill, Cr.; Yip, D.; Zalcberg, J.R.; Tu, D.; Goodwin, R.A.
Abstract Background Right- and left-sided colon cancers (RC, LC) differ with respect to biology, pathology and epidemiology. Previous data suggest a mortality difference between RC and LC. We examined if primary tumour side also predicts for outcome in chemotherapy refractory, metastatic colon cancer (MCC). We also compared RC versus LC as a predictor of efficacy of epidermal growth factor receptor (EGFR) inhibition with cetuximab. Methods Reanalyzing NCIC CO.17 trial (cetuximab versus best supportive care [BSC]), we coded the primary tumour side as RC (caecum to transverse colon) or LC (splenic flexure to rectosigmoid). The association between tumour side and baseline characteristics was assessed. Cox regression models determined factors affecting overall survival (OS) and progression free survival (PFS). Results Patients with RC (150/399) had more poorly differentiated, mutant KRAS, mutated PIK3CA and wild-type BRAF tumours, fewer liver and lung metastases, and shorter interval between diagnosis and study entry. Among BSC patients, tumour side was not prognostic for PFS (hazard ratios (HR) 1.07 [0.79–1.44], p = 0.67) or OS (HR 0.96 [0.70–1.31], p = 0.78). Among wild-type KRAS patients, those with LC had significantly improved PFS when treated with cetuximab compared to BSC (median 5.4 versus 1.8 months, HR 0.28 [0.18–0.45], p < 0.0001), whereas those with RC did not (median 1.9 versus 1.9 months, HR 0.73 [0.42–1.27], p = 0.26), [interaction p = 0.002]. Conclusion In refractory MCC, tumour location within the colon is not prognostic, but is strongly predictive of PFS benefit from cetuximab therapy. Additional research is needed to understand the molecular differences between RC and LC and their interaction with EGFR inhibition.